Intra-and Inter-Observer Accuracy of Cobb’s Angle in Scoliosis; Six Weeks Apart (Journal of Pakistan Orthopaedic Association, 2024)
Objective: Cobb’s angle is important for assessing the severity and progression of the curvature, as well as for monitoring and managing spine deformities. The reliability in the determination of Cobb's angle depends on the technical expertise of the observer, as well as on the correct angle measurement and determination of the end vertebra. This study was aimed to find inter and intra observer variations while measuring cobb’s angle on same radiographs 6 weeks apart.Methods: A Prospective cohort study of total of 39 radiographs were studied and each observer with a different level of experience measured the same radiographs. Measurements were taken by trained observers at two time points, six weeks apart by five different readers with different years of experience, to check the accuracy in terms of years of experience at 6 weeks’ interval at Dr. Ziauddin Hospital Karachi.Results: The mean differences in Inter-observer Cobb's angle recorded among raters ranged from 2.1° to 13.2° whereas the mean Intra-Observer Cobbs angle ranged from 2.31° to 10.15° when measuring on the same PA radiographs.Conclusion: The reliability in the determination of Cobb's angle depends on the technical expertise of the observer, as well as on the correct angle measurement and determination of the end vertebra. However, even with the same end vertebra used as a reference, Cobb's measurement may vary.